Nové trendy v diagnostice a lécbe systémové sklerodermie - Becvár, R; Stork, J; Jansa, P (Vnitrni lekarstvi, 2006)
Systemic sclerosis (SSc) is a generalised connective tissue disease of unknown origin, which clinically shows by skin thickening and sclerosis of different extent (scleroderma) and by typical involvement of visceral organs. At the same time fibrotic and sclerotic changes occur in the blood vesel walls. SSc usually involves females at young and middle age. Myalgias, arthralgias and arthritis are nonspecific, tendon friction rubs in fingers are more typical for this diagnosis. Gastrointestinal involvement starts early in the oropharyngeal part, esophagus and proceeds into the distal parts. Fibrotic changes lead to slow transit dysmotility and pseudoobstruction and/or dilation of the bowels. The main symptoms are dysphagia, pyrosis, malabsorption and constipation. SSc produces two major patterns of abnormality within the lungs a fibrosing alveolitis or a primary pulmonary vascular disease. More frequently an insterstitial process develops which can be followed by pulmonary arterial hypertension. Cardiac involvement can also have different forms. Myocardial fibrosis usually appears at first in the conduction system by arrhythmias and various conduction blocks while pericarditis is mostly asymptomatic. Renal manifestation of SSc is observed in 8-10% patients. The most severe form--scleroderma renal crisis is characterised by the new onset of accelerated hypertension and rapidly progressive oliguric renal failure. No therapies have been proven to modify the course of SSc. Some of the drugs can affect only the skin changes. Majority of the currently applied agents have only a symptomatic effect.
Keywords: prognóza; Prognosis; systémová sklerodermie; lidé; Scleroderma, Systemic; Humans